Implementasi Cross Selling dalam Meningkatkan Loyalitas Nasabah di Perbankan Syariah: Studi Kasus Pada Bank Sumut Syariah Cabang Padangsidimpuan - Lilia Afriani; Muhammad Lathief Ilhamy Nasution (Universitas Muhammadiyah Enrekang, 2023)
This study aims to conduct in-depth analysis and discussion related to the implementation of cross-selling in increasing customer loyalty. This research was conducted at Bank Sumut Syariah, Padangsidimpuan branch. The research method used is descriptive qualitative method of collecting data through observation and in-depth interviews. The analysis was carried out using the Miles and Huberman triangulation method. The results of the analysis show that the implementation of cross-selling in increasing customer loyalty is measured using three indicators, namely continued use, recommendations to other people and resistance not to move to another bank. Based on the indicators of continuing use and recommendations to other people, the implementation of cross-selling can increase customer loyalty because customers continue to use bank products and recommend Bank Sumut Syariah products offered through cross-selling. While the third indicator, namely resilience not to move to another good, through the implementation of cross-selling cannot increase customer loyalty. This is because customers also take advantage of cross-selling products at other banks for certain financial transactions.